2020
DOI: 10.1071/bt19124
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phenolics in populations of Teucrium chamaedrys (Lamiaceae) from serpentine soils

Abstract: The genus Teucrium includes perennial herbs or shrubs widespread all around the world. The wall germander (Teucrium chamaedrys L.) is widely used in traditional and modern medicine for various health disorders and recent research revealed that serpentine populations of this herb have increased antioxidant and respective medical potential compared with calcareous population. The present study aims to elucidate further the role of phenolic compounds for T. chamaedrys growth on serpentine soil. Methanol extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The procedures for spectrophotometric quantification of phenolics and flavonoids are described by Zhiponova et al ( 2020b ), and performed with spectrophotometer Shimadzu UV 1800 (Kyoto, Japan). The content of polyphenols was determined according to Singleton et al ( 1999 ) by a standard curve created using the known concentrations of gallic acid (GA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures for spectrophotometric quantification of phenolics and flavonoids are described by Zhiponova et al ( 2020b ), and performed with spectrophotometer Shimadzu UV 1800 (Kyoto, Japan). The content of polyphenols was determined according to Singleton et al ( 1999 ) by a standard curve created using the known concentrations of gallic acid (GA).…”
Section: Methodsmentioning
confidence: 99%
“…A study on the antiparasitic activity showed a very high potential of methanol and hexane extracts of N. nuda against the parasite Tripanozoma brucei rhodesiense without having toxic side effects on the host cells (Kirmizibekmez et al, 2011 ). Environmental factors such as light, temperature (Alberti, 2020 ; Zhiponova et al, 2020a ), and soil composition (Pádure et al, 2008 ; Zhiponova et al, 2020b ), additionally affect plant growth and biosynthetic potential. Compared to wild-grown plants, the in vitro cultivation ensures controlled and sterile conditions on a nutrient medium of known composition.…”
Section: Introductionmentioning
confidence: 99%
“…The radical-scavenging capacity of the extracts and their total antioxidant activity again showed the highest levels in the leaves (17 and 52 mM g DW −1 , respectively). A previous report correlated the antioxidant properties of the medicinal plant Teucrium chamaedrys with the content of phenolic acids, while flavonoids were suggested to be involved in photoprotection and temperature-response regulation [23]. In stems, the antioxidant activity was weaker, and in roots, it was generally absent (Figure 1e).…”
Section: Pigments Reducing Sugars Proteins and Antioxidantsmentioning
confidence: 73%
“…Plant material was used for preparation of crude methanol extracts (10 mg mL −1 ) by homogenization and ultrasonication. The procedures for spectrophotometric quantification of phenolics and flavonoids and antioxidant activities (total antioxidant activity, TAA, and radical-scavenging activity using stable 2,2 -diphenyl-1-picrylhydrazyl, DPPH, free radical) were described by Zhiponova et al [23] and Petrova et al [54]. The content of polyphenols was determined according to Singleton et al [55] by a standard curve created using the known concentrations of gallic acid (GA).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…In ex vitro, acclimated V. caucasica plants predominated the protocatechuic acid (3,4-dihydroxybenzoic acid), which was identified as a main compound in the phenolics pool in V. montana, showed effective antibacterial activity against six pathogenic bacteria and was successfully used to preserve cream cheese by inhibiting the growth of Listeria monocytogenes [39]. In ex vitro conditions, the plants are exposed to more severe environmental changes that require the synthesis of phenolic compounds to aid the plant adaptation [40]. Poland).…”
Section: Metabolite Profiling During V Caucasica Ex Situ Conservationmentioning
confidence: 99%